Prediction of protective sensory loss, neuropathy and foot ulceration in type 2 diabetes. Issue 1 (6th May 2016) - Paisey, R B; Darby, T; George, A M; Waterson, M; Hewson, P; Paisey, C F; Thomson, M P
Abstract : Objectives: To prospectively determine clinical and biochemical characteristics associated with the development of peripheral neuropathy, loss of protective sensation, and foot ulceration in persons with type 2 diabetes mellitus (DM) over 7 years. Research design and methods: Graded monofilament (MF) testing, vibration perception threshold, and neuropathy symptom questionnaires were undertaken in 206 participants with type 2 DM without peripheral vascular disease or history of foot ulceration and 71 healthy participants without DM at baseline and after 7 years. 6 monthly glycosylated hemoglobin (HbA1c) levels and annual serum lipid profiles were measured during follow-up of those with DM. Incident foot ulceration was recorded at follow-up. Results: Taller stature and higher quartiles of serum triglyceride and HbA1c levels were associated with neuropathy at follow-up (p=0.008). Remission of baseline neuropathy was observed in 7 participants at follow-up. 9 participants with type 2 DM developed foot ulcers by the end of the study, only 1 at low risk. Mean HbA1c levels were higher in those who developed foot ulceration (p<0.0001). 1 participant with neuropathy throughout developed a Charcot foot. Failure to perceive 2 or more 2, 4 and 6 g MF stimuli at baseline predicted loss of protective sensation at follow-up. Conclusions: Tall stature and worse metabolic control were associated with progression to neuropathy. Mean HbA1c levels were higher in those who developed foot ulcers. Graded MF testing may enrich recruitment to clinical trials and assignation of high risk for foot ulceration.